Publishing Provenance-rich Scientific Papers - Bauer, Bela; Gukelberger, Jan; Surer, Brigitte; Troyer, Matthias (TaPP, 2011)
Complete documentation and reproducibility of results are important goals for scientific publications. Standard scientific papers, however, usually contain only final results and document only parameters and processing steps that the authors considered important enough. By recording the complete provenance history of the data leading to a publication one can overcome this limitation and allow reproducibility for reviewers, publishers and readers of scientific publications. While the process of capturing provenance information is a growing research subject, here we discuss usually overlooked challenges involved in publishing provenance-complete papers. We report on our experience in preparing and publishing two specific executable papers where we used the VisTrails workflow system to embed full provenance information of the paper and discuss open challenges and issues we encountered.